Role of plant extracts and essential oils in fighting against postharvest fruit pathogens and extending fruit shelf life: A review - El Khetabi, A.; Lahlali, R.; Ezrari, S.; Radouane, N.; Nadia, L.; Banani, H.; Barka, E. A.
Background. Worldwide, fruit and vegetable production is permanently affected by many threats including microbial pathogens. Among them, different fungal pathogens cause severe symptoms on fruits in pre- and postharvest. During postharvest, multiple attempts have been made to control the microbial decay of fresh horticultural commodities by using alternatives to synthetic fungicides, which threaten environment and human health. Among these, the use of natural plant products such as plant extracts, essential oils and microbial antagonists has emerged as being the most promising ecological alternative over the last 20 years. Scope and approach.There are more than 250,000 plant species worldwide that could be tested for their volatile molecules or bioactive compounds and their biological activity towards microbial species causing postharvest diseases. However, despite their effects against several phytopathogenic fungi, oomycetes and bacteria, the use of plant extracts and essential oils (EOs)in agriculture remains surprisingly limited. Key findings and conclusions The aim of the present review is to gather and discuss up-to-date reports in the scienti?c literature on the biological activity of EOs and plant extracts against postharvest pathogens. Advances and challenges concerning the innovative methods, potentially valuable to improve the efficiency and reliability of EOs, have been reviewed to find efficient alternative strategies to synthetic fungicides in the control of fruit rot pathogens.
Keywords: PLANT EXTRACT; ESSENTIAL OIL; POSTHARVEST PATHOGEN; SYNTHETIC FUNGICIDES